Pretreatment of Natural Materials Used for Supercritical Fluid Extraction of Commercial Phytopharmaceuticals. Issue 9 (6th August 2014) - Ivanovic, Jasna; Meyer, Florian; Stamenic, Marko; Jaeger, Philip; Zizovic, Irena; Eggers, Rudolf
Abstract A proper method was to be developed for the pretreatment of different types of natural materials in order to increase the efficiency of supercritical fluid extraction (SFE) regarding yield and active substance content. The effects of different mechanical pretreatments were investigated: flaking, impact plus shearing, and cutting plus grinding. Additionally, the influence of intermediate rapid gas decompression was studied. Significant effects of the applied pretreatments on the yield (increase by up to 1350 %) were shown for SFE of selected oilseeds, artemisia aerial parts, and the lichen Usnea barbata. Flaking was the most effective pretreatment for increasing the yield of SFE of fennel seeds, artemisia aerial parts, and Usnea lichen, while impact plus shearing was optimal for processing amaranth, milk thistle, and oat seeds. The use of defined optimal pretreatments led to notable increases in the contents of usnic acid (50 %) and artemisinin (300 %).